6 uždavinys

5 uždavinys7 uždavinys

Išspręskite lygtį (x + 2011)(x + 2013)(x + 2014) = (x + 2013)(x + 2014)(x + 2015).

A - 2011; - 2013; - 2014; - 2015

B  - 2011; - 2015

C  - 2013;  - 2014

D sprendinių nėra

Sprendimas:

 (x+2011)* (x+2013)* (x+2014)  = 
 (x+2013)* (x+2014)* (x+2015)
 (x+2011)* (x+2013)* (x+2014) =  (x+2013)* (x+2014)* (x+2015) = 
 (x+2011)* (x+2013)* (x+2014)- (x+2013)* (x+2014)* (x+2015) = 0 = 0
=
Paaiškinimas:
(x + 2013) * (x + 2014) iškeltas prieš skliaustus
 (x+2013)* (x+2014)* ((x+2011)-(x+2015)) = 0 = 0
=
 (x+2013)* (x+2014)* (x+2011-(x+2015)) = 0 = 0
=
 (x+2013)* (x+2014)* (x+2011-x-2015) = 0 = 0
 (x+2013)* (x+2014)* (x-x+2011-2015) = 0 = 0
= 0
 (x+2013)* (x+2014)* (0+2011-2015) = 0 = 0
 (x+2013)* (x+2014)* (2011-2015) = 0 = 0
=
 (x+2013)* (x+2014)* (-4) = 0 = 0
 (x+2013)* (x+2014) = 0 = 0
x+2013 = 0 = 0
x = -2013+0 = 
x = -2013 = 
x+2014 = 0 = 0
x = 0-2014 = 
x = -2014 = 

Atsakymas: C  - 2013;  - 2014

5 uždavinys7 uždavinys